Prevalence and significance of subcentimeter hepatic lesions in patients with localized pancreatic adenocarcinoma - Elnahal, Shereef M. (Pract Radiat Oncol, 2012)
OBJECTIVES: To determine the prevalence and significance of incidental hepatic and pulmonary sub-centimeter lesions in patients with localized pancreatic cancer. METHODS: This retrospective study included 101 patients treated for localized pancreatic adenocarcinoma from 1999 to 2007. Staging and follow-up imaging was reviewed to determine the frequency of sub-centimeter liver and pulmonary lesions. Using Cox regression, we calculated adjusted hazard ratios (HR) to determine the association between presence of liver and pulmonary lesions and overall survival. RESULTS: Forty patients (39.6%) had sub-centimeter hepatic or pulmonary lesions on staging scans. Of these patients, 33 (82.5% of patients with lesions) had eventual metastases in the same organ as the lesions. Of this group, seven patients (17.5% of patients with lesions) eventually had a metastasis at the site of the original lesion. Liver lesions predicted the occurrence of metastatic disease to the liver compared to patients without lesions (67.7% with lesions vs. 44.4% without, p = .034). Sub-centimeter liver lesions at diagnosis were significantly associated with reduced overall survival (HR 1.65, p = 0.036). CONCLUSIONS: Sub-centimeter lesions in the liver and lung are common in patients with localized pancreatic cancer. The presence of indeterminate lesions may be associated with reduced overall survival.